STRUCTURAL STATTIC ANALYSIS OF TIN DREDGER WITH ELASTIC FOUNDATION MODEL - (NIM : 13107123); Dosen Pembimbing : Rachman Setiawan, ST, M.Sc.,Ph.D., ERWIN
Dredger is a ship that is devoted to dredging activities in the waters. The function of dredge is to block, lift and move material such as soil, sand and rocks from the layers that form a crust on the seafloor. In a case study in this Bachelor task, operating location of tin dredges is moved from lake to offshore. With changes in environtmental and operational loading conditions, the strength of the vessel need to be analyzed to determine the feasibility of the vessel to operate offshore from the aspect of structural strength. Activities undertaken include the analysis of static load to determine the maximum stress that occurs in the structure. Analyses were performed with analytical methods based on Germanisher Lloyd Rules. Based on this method, the maximum stress that occurs on pontoon is 382 MPa, so GL Rules states that the ship is not feasible to operate. This is due to GL Rules only take into account the shipÃ‚Â’s hull to determine the strength of the structure. As for dredger, the upper structure have enough contribution to be taken into account when determining the strength of the ship. Because of that, Finite Element Method is used so that the strength of the whole structure is taken into account. Water surface foundation is elastic, the deeper an object submerged in water, the greater reaction force that occurs. Hence, water surface foundation is modeled as springs that have similarity in principle. In the analysis with calm water constraint for some ladder positions, the maximum stress that occurs is 216 MPa, smaller than the yield strength of the material. In the analysis with wavy water constaint for some ladder positions, the maximum stress that occurs reaches 240MPa to 290MPa. Based on this analysis, in order to operate offshore, the dredger need to be modified in areas that fails. The modification can be changes in beam material, use larger beam size , or spread the stress that occurs with addition of beam.